Phytochemical and Antibacterial Screening of Euphorbia thymifolia Linn and Cassia alata Linn Species in the Province of Abra, Philippines: An Alternative Source of Antibiotics - Paderes, Nero M.; Eloisan, Divinia Borgona (JPAIR Multidisciplinary Research, 2016)
Plants have been aiding humanity around the world by serving as an abundant source of valuable drugs, antibiotics, nourishment, spices, seasonings, dyes, and other commercial and industrial products. The study investigated the antibacterial activity and phytochemical screening of Cassia alata Linn and Euphorbia thymifolia Linn ethanolic extracts against Staphylococcus aureus and Escherichia coli. The research was laid out using Complete Randomized Design (CRD) which was replicated three times. Varying concentrations of Cassia alata Linn and Euphorbia thymifolia Linn ethanolic extracts at 75%, 50% and 25% concentrations were utilized for the antimicrobial assay using the Kirby Bauer method. Phytochemical analysis revealed the presence of phenolics in both plants and some other bioactive components that have been found in vitro to have antibacterial properties. Statistical analysis using ANOVA and DMRT at .05 level of significance shows that among the two plants tested, Euphorbia thymifolia Linn ethanolic extract at 75% concentration exhibited a significant mean diameter of zone of inhibition against Staphylococcus aureus and Escherichia coli. Further laboratory analysis and testing should be conducted through the Bureau of Food and Drugs (BFAD) for further confirmatory results.